Interpretasi dan Pengembangan Hukum Islam dalam Konteks Perkembangan Zaman - Sumarta, Sumarta; Burhanudin, Burhanudin; Zamzami, Zamzami (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2024)
Interpreting and developing Islamic law in the context of evolving times is a crucial issue within the realm of Islamic jurisprudence. This article delves into how Islamic law has undergone transformation and adaptation over time to address the challenges faced by the Muslim community in the modern society. The interpretation of Islamic law has become the primary focus of scholars and theologians, aiming to understand Islamic teachings and apply them in a relevant manner within contemporary circumstances. Confronting the changes of the times, it is imperative to consider the fundamental principles of Islamic law, such as ijma' (consensus), qiyas (analogy), and ijtihad (personal interpretation), as tools for developing Islamic law to remain pertinent and in line with the demands of the era. This article also examines various approaches and methods employed in the effort to interpret and develop Islamic law, including the roles of fatwa institutions and Islamic legal bodies in this process. By comprehending how Islamic law can adapt to the evolution of time, we can establish a more inclusive and responsive framework to meet the needs of the modern Muslim society while upholding the core values and principles of the Islamic faith.